Highly efficient CuOx/OMS-2 catalyst for synthesis of phenoxathiin derivatives via intramolecular arylations of phenols with aryl halides. Issue 46 (14th November 2019) - Liu, Na; Chao, Fei; Huang, Yu; Wang, Yanlan; Meng, Xu; Wang, Long; Liu, Xiang
Graphical abstract: Highlights: Phenoxathiin has attracted many interest due to its properties and wide applications. CuOx/OMS-2 catalyzed synthesis of phenoxathiinan derivatives has been achieved. The catalyst has been successfully recycled 8 times by the simple filtration. Abstract: Phenoxathiin and its derivatives have attracted a great deal of interest due to their unique chemical and physical properties and their applications in fluorescent materials, antifungal activities and selective inhibitors. In the presence of copper supported on manganese oxide-based octahedral molecular sieves OMS-2 (CuOx /OMS-2), the heterogeneously catalytic synthesis of phenoxathiinan derivatives via intramolecular arylations of phenols with aryl bromide or aryl chloride has been achieved. TEM and XRD have confirmed the CuOx /OMS-2 catalyst has been successfully reused 8 times without a significant decrease in the yield, with simple filtration and washing as a means of separation.